Restless Legs Syndrome: A Unique Case and Essentials of Diagnosis and Treatment - Agarwal, Pinky (Medscape, 2008)
Restless legs syndrome (RLS) is a common, poorly understood movement disorder that can cause significant sleep disruption. RLS is characterized by uncomfortable sensations deep in the legs, relieved only by voluntary movement. Differential diagnosis includes peripheral neuropathy, leg cramps, and akathesia. Although RLS is familial in 50% of cases, secondary etiologies can be medically important, such as iron deficiency anemia and renal failure. We report a rare case of RLS associated with hyperparathyroidism. To our knowledge, only 1 other case of hyperparathyroid-related RLS has been described.